Adding aromatic herbs in the elaboration of a carbonated drink based on passion fruit - Cedeño Barre, Rubén Fabricio; Gorozabel Muñoz, Wagner Antonio (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Generally, companies have limited themselves to offering products based on artificial additives, leaving the consumer dissatisfied, who, driven by preferences for healthier products, seeks a drink with better sensory and nutritional characteristics. In this work, a carbonated drink based on passion fruit (Passiflora edulis) was prepared with the addition of the aromatic herbs peppermint (Mentha spicata), lemon verbena (Cymbopogon citratus) and ginger (Zingiber officinale), at three concentrations (1, 3 and 5%). To identify physicochemical and sensory differences in the elaborated beverages, the physicochemical parameters °Brix, acidity, pH and CO2 volume were evaluated, based on the NTE INEN 1101-2017 and were subsequently subjected to an acceptability test by thirty untrained judges. A completely randomized bifactorial AxB design was used, for the comparison of means the Tukey al test was used (p <0.05). For the analysis of results, non-parametric statistics were used using the KRUSCAL WALLIS test and the Mann Whitney U test was used to determine the difference in means. The results of the ANOVA for the physicochemical parameters showed statistical significance (p˂0.05) for the °Brix and pH; and for the variables acidity and volume of CO2, no statistically significant differences were observed (p> 0.05). The drink made with lemon verbena at 3% presented a higher concentration of soluble solids with a value of 14.03 °Brix, and pH of 3.08, showing that these results comply with the parameters established by the standard. Sensorially, the drink made with lemon verbena at 1% obtained a better acceptance with respect to taste by the panelists.